2021
DOI: 10.21203/rs.3.rs-888984/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study on perception on HIV infection and prevention among religious leaders of Presbyterian Church, Aizawl, Mizoram

Abstract: Aim of the study is to find the perceptions of Presbyterian Church leaders about HIV prevention in Aizawl, Mizoram. For the study, mixed method was followed for data collection. From 15 Presbyterian churches, 293 Church leaders representing four groups, that is, Pastor/Elder, Women, Youth and Men were randomly selected and used self-administered questionnaire for the purpose of understanding perceptions on HIV prevention from them. Chi-square test was done to understand the associations with different factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Church leaders are willing to disseminate sex education, including the use of condoms, to their youth. Approximately, 80% of church leaders reported that condoms prevent HIV, and they passed that message to their congregants (Ralte 2021 ). This might send negative message to the youth that they should engage in sexual activities using condoms, which might also carry some risk of contracting HIV in case the condom is not correctly used or if it bursts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Church leaders are willing to disseminate sex education, including the use of condoms, to their youth. Approximately, 80% of church leaders reported that condoms prevent HIV, and they passed that message to their congregants (Ralte 2021 ). This might send negative message to the youth that they should engage in sexual activities using condoms, which might also carry some risk of contracting HIV in case the condom is not correctly used or if it bursts.…”
Section: Discussionmentioning
confidence: 99%
“…Prevention, support and treatment were also mentioned by the research participants as the strategy of the church for combating the spread of HIV. Most religious leaders expressed their willingness to contribute to HIV prevention and give support to those who are already infected by the disease (Ralte 2021 ). Church leaders have implemented a variety of activities, including encouraging people to seek treatment, providing care and support to people living with HIV and disseminating prevention messages to the youth (Williams et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the initial phase of the 20th century, the issue regarding the eastern boundary of Tripura created great controversy, and the area was quite uninhabited; the Mizos (Lushai), under a Sailo chief, Dokhuma-Sailo, migrated to Tripura from the Lushai hills with the permission of the Maharaja of Tripura. It is believed that they did so in search of better Jhum land (Ralte, 2015). In the upper region of Vanghmun, a small monument built in memory of Chief Dukhuma Sailo can be sighted; it was built by his descendants and people of the tribes to honour him.…”
Section: Socio-culturementioning
confidence: 99%
“…The present findings are consistent with the study of Chanchpara et al reported that noise level was reported to be maximum during night-time compared with the morning time [36]. This indicates that fireworks activities are extensively carried out during the night time.An increase in noise levels during Diwali celebrations can lead tosleep disturbance, high blood pressure, and temporary or permanent hearing loss [63].…”
Section: Variation Of Gas Pollutants (Co Co2and Tvoc) Concentrationsmentioning
confidence: 99%